PENGARUH DIVERSITAS DEWAN DIREKSI DAN OVERCONFIDENCE TERHADAP TAX AVOIDANCE (SURVEI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016) - Anjani, Fatima Tria (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to examine and analyze the effect of gender diversity, Javanese culture, age, and overconfidence on tax avoidance, a legal conduct to avoid tax payment by way of tax planning to reduce tax that should be paid. Tax avoidance results in losses for the government because tax contribution from companies is not optimal. The data of this study are secondary data from a sample of 172 manufacturing companies listed in the Indonesia Stock Exchange, selected through purposive sampling method, in the period 2013-2016. Using multiple regression analysis, the results show that gender diversity and overconfidence have a significant effect on tax avoidance, but Javanese culture and age diversity of directors do not affect tax avoidance.Keywords: gender diversity, Javanese culture, age diversity , overconfidence, tax avoidance